2014
DOI: 10.1016/j.biopsych.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Exerts Dose-Dependent Effects on Glutamate Receptors and Behaviors

Abstract: Background Methylphenidate (MPH), a psychostimulant drug for the treatment of attention-deficit hyperactivity disorder (ADHD), produces the effects of increasing alertness and improving attention, while its misuse has been associated with an increased risk of aggression and psychosis. In this study, we sought to determine the molecular mechanism underlying the complex actions of MPH. Methods Adolescent (4-week-old) rats were given one injection of MPH at different doses. The impact of MPH on glutamatergic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 56 publications
3
61
0
2
Order By: Relevance
“…All these events could be related to detriment of synaptogenesis and maturation of functional synaptic connectivity in the hippocampus of juvenile rats treated with MPH. In agreement with our result, Cheng et al [60] showed that SNAP-25 has important role on behavioral, electrophysiological, and biochemical changes promoted by MPH. However, we cannot rule out the hypothesis that the reduction of SNAP-25 immunocontent in the hippocampus of juvenile rats exposed to chronic treatment with MPH may be a way that the body found to protect themselves from the toxic effects of increased release of neurotransmitters (glutamate, dopamine, noradrenaline, and others) in the synaptic cleft and/or a consequence of the reduction of neurons.…”
Section: Discussionsupporting
confidence: 95%
“…All these events could be related to detriment of synaptogenesis and maturation of functional synaptic connectivity in the hippocampus of juvenile rats treated with MPH. In agreement with our result, Cheng et al [60] showed that SNAP-25 has important role on behavioral, electrophysiological, and biochemical changes promoted by MPH. However, we cannot rule out the hypothesis that the reduction of SNAP-25 immunocontent in the hippocampus of juvenile rats exposed to chronic treatment with MPH may be a way that the body found to protect themselves from the toxic effects of increased release of neurotransmitters (glutamate, dopamine, noradrenaline, and others) in the synaptic cleft and/or a consequence of the reduction of neurons.…”
Section: Discussionsupporting
confidence: 95%
“…Thus, catecholamines exert receptor-dependent modulation of excitatory and inhibitory amino acid signaling in a variety of brain regions (8789), including the PFC (90,91). In the PFC, NMDA-receptor mediated excitatory postsynaptic currents (EPSCs) are potentiated by a cognition-enhancing dose of MPH, an action that involves D1 receptors (8991). Moreover, at least a subset of catecholamine actions in the PFC is linked to the modulation of hyperpolarizationactivated cyclic nucleotide (HCN) channels (92).…”
Section: Receptor Mechanisms In the Pfc: Ne α2 And Da D1 Receptorsmentioning
confidence: 99%
“…In contrast, suppressive effects of high dose psychostimulant on evoked discharge of PFC neurons (reduced by ~80%; Figure S2; 6) involve D1-mediated activation of HCN channels and/or α1-mediated activation of SK channels (92). Additionally, psychostimulant-driven reductions in evoked discharge may involve suppression of glutamatergic signaling, as high doses of MPH (8.0 mg/kg) suppress both NMDA and AMPA-receptor mediated EPSCs (89). …”
Section: Receptor Mechanisms In the Pfc: Ne α2 And Da D1 Receptorsmentioning
confidence: 99%
“…Our previous studies in rodents have found that D4R activation modulates NMDAR trafficking and function (Wang et al, 2003), and this modulation goes awry in a schizophrenia model (Wang et al, 2006). Administration of methylphenidate (MPH), a dopamine and norepinephrine reuptake inhibitor approved for ADHD treatment, facilitates attention by potentiating PFC NMDAR function (Cheng et al, 2014). These animal studies prompt us to speculate that the ADHD-linked human D4R variants may induce ADHD-like behaviors via dampening NMDAR function through the aberrant interaction with NMDAR/PSD-95 complex.…”
Section: Introductionmentioning
confidence: 99%